Effects of sulfur mustard on mesenchymal stem cells. (1st September 2018) - Schmidt, Annette; Steinritz, Dirk; Rothmiller, Simone; Thiermann, Horst; Scherer, A. Michael
Highlights: MSCs are able to repair S-Lost-induced alkylation. This repair is probably done via the DDR system. Reduction of apoptosis and proliferation is combined with increased of SAβ-Gal-positive cells. This combination suggests a transformation of the cells into a senescent state. Abstract: Chronic wound healing disorders that occur as a result of a sulfur mustard (SM) exposure present a particular challenge. These chronic wounds are similar to other chronic wounds. In the past, it has been shown that mesenchymal stem cells (MSC) play an important role in the healing of chronic wounds. An important property to support wound healing is their ability to migrate. However, we were able to show that SM leads to a reduction in MSC migration even at low concentrations. Currently, exposed MSCs are still able to differentiate. Further alterations are not known. The current investigation therefore focused onto the question how SM affects MSC. Material & methods: The effect of SM on MSC was investigated. Here, the alkylation of DNA was considered, and DNA adducts were quantified over a period of 48 h. The modification of the nuclei under the influence of SM was analyzed as well as proliferation of the cells by immunohistochemical staining with Ki-67 and quantification. For the quantification of the apoptosis rate, antibodies against cleaved Caspase-3, 8, and apoptosis inducing factor (AIF) were used. The senescence analysis was performed after histological staining against β-galactosidase. Quantifications were carried out by using the TissueQuest System and the software TissueFAX. Results: SM exposure of MSC results in a dose dependent formation of nuclear DNA adducts. 4 h after exposure the cells display a decreasing concentration of DNA adducts. This process is accompanied by a change of nuclei shape but without an increase of apoptosis induction. In parallel the number of cells undergoing senescence increases as a function of the SM concentration. Discussion: SM exposure of MSC leads to adduct formation on chromosomal DNA. These DNA adducts can be reduced without MSC are undergoing apoptosis. This indicates an active DNA damage response (DDR) pathway in combination with the formation of persistent nuclear DNA damage foci. This process is accompanied by a reduced capability of proliferation and a transition into the senescent state.